2005
DOI: 10.1121/1.2005847
|View full text |Cite
|
Sign up to set email alerts
|

Transmission properties of bone conducted sound: Measurements in cadaver heads

Abstract: In the past, only a few investigations have measured vibration at the cochlea with bone conduction stimulation: dry skulls were used in those investigations. In this paper, the transmission properties of bone conducted sound in human head are presented, measured as the three-dimensional vibration at the cochlear promontory in six intact cadaver heads. The stimulation was provided at 27 positions on the skull surface and two close to the cochlea; mechanical point impedance was measured at all positions. Cochlea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

37
268
1
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 210 publications
(308 citation statements)
references
References 35 publications
37
268
1
2
Order By: Relevance
“…3 the difference between ECSP and thresholds originated in the threshold measurements where a dip in the transcranial transmission was seen at 0.5 kHz whereas the ECSP were similar irrespective if stimulation was ipsilateral or contralateral. The relatively higher sensitivity from ipsilateral stimulation was not easily explainable when similar results were neither seen in the current ECSP measurement nor in cochlear vibration measurement executed previously in cadaver heads (Stenfelt and Goode, 2005a). However, in the Stenfelt and Goode (2005a) study it was concluded that the response vibration direction of the cochlea was different when the stimulation was close (ipsilateral mastoid) than when it was further away (e.g.…”
Section: Difference Between Ear-canal Sound Pressure and Hearing Thresupporting
confidence: 55%
See 4 more Smart Citations
“…3 the difference between ECSP and thresholds originated in the threshold measurements where a dip in the transcranial transmission was seen at 0.5 kHz whereas the ECSP were similar irrespective if stimulation was ipsilateral or contralateral. The relatively higher sensitivity from ipsilateral stimulation was not easily explainable when similar results were neither seen in the current ECSP measurement nor in cochlear vibration measurement executed previously in cadaver heads (Stenfelt and Goode, 2005a). However, in the Stenfelt and Goode (2005a) study it was concluded that the response vibration direction of the cochlea was different when the stimulation was close (ipsilateral mastoid) than when it was further away (e.g.…”
Section: Difference Between Ear-canal Sound Pressure and Hearing Thresupporting
confidence: 55%
“…Recently, the transcranial attenuation was estimated for two stimulation positions (one close to the ear-canal opening and the other further back) by hearing thresholds (Stenfelt, 2012). In the same study the results were compared with estimations from vibration of the cochlea in cadaver heads using one-dimensional velocity measurements (Eeg-Olofsson et al, 2011) and three-dimensional acceleration measurements (Stenfelt and Goode, 2005a). According to Stenfelt (2012), average perceptual measures were close to the vibration estimates at frequencies between 0.8 and 6 kHz.…”
Section: Introductionmentioning
confidence: 90%
See 3 more Smart Citations